PENGARUH DEBT TO EQUITY RATIO, RETURN ON ASSETS DAN PRICE TO BOOK VALUE TERHADAP RETURN SAHAM PADA PERUSAHAAN SUB SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI - Putri, Lodia Dwika; Nurmansyah, Nurmansyah; Aznuriyandi, Aznuriyandi (Jurnal Akuntansi Kompetif, 2024)
This study aims to analyze the effect of Debt To Equity Ratio, Return On Assetss, and Price To Book Value on Stock Return. The population in this study are all property and real estate sub-sector companies listed on the Indonesia Stock Exchange in 2019-2021. Sampling was carried out using a purposive sampling method and 14 companies were selected. The analysis technique used is the multiple linear regression method, data quality test, classical assumption test, model goodness of fit test and individual parameter significance test. The results showed that the Debt To Equity Ratio and Price To Book Value had an effect on Stock Return, while Return On Assetss had no effect on Stock Return. The close relationship that occurs between the variables Debt To Equity Ratio, Return On Assetss, and Price To Book Value is quite strong with a correlation coefficient of 50.5% and the contribution of the independent variable to the dependent variable is 19.7% while 80.3% is influenced by other variables that are not included in this research method. Keyword: Debt To Equity Ratio, Return On Assets , Price To Book Value, and Stock Return.